Effects of climate and latitude on age at maturity and longevity of lizards studied by skeletochronology - Cabezas, Facundo (2018)
Synopsis Longevity and age at maturity are key life-history traits, directly linked to fitness attributes such as survival and reproductive output. It has been proposed that these traits are strongly influenced by environmental factors, such as temperature, seasonality, and precipitations, which determine the existence of a continuum of life-histories that goes from the "slow" life histories characterized by late maturity and high longevity of cold and highly seasonal climates to the "fast" life histories characterized by early maturity and low longevity, typical of the tropical climates. However, largescale studies that address these topics in lizards are scarce and most of them are based on heterogeneous data, which may overlook the real patterns. Using skeletochronology, we studied age at maturity and longevity of two species of Phymaturus lizards, Phymaturus aguanegra from the Andes and Phymaturus zapalensis from the Patagonian steppe (Argentina). Then, we confronted longevity and age at maturity in these species with published skeletochronologybased data on 46 other lizard species to examine possible association of these life-history traits with latitude and mean annual temperature, thermal amplitude, and precipitations. Both Phymaturus species showed late sexual maturity (7 and 8-9 years, respectively) and high longevity (16 and 14-15 years, respectively) in coincidence with the other species of the genus studied up to date. The phylogenetic comparative analysis revealed that the most important variable in the determination of longevity patterns in the species studied was latitude: at higher latitudes lizards tend to live longer. In contrast, age at sexual maturity was dependent on mean annual temperature most, especially in males, as lizards from hotter climates mature earlier than lizards from cold sites.